اسلام میں خوشی کا تصور:ایک مطالعہA Study of the Concept of Happiness in Islam (Al-Qamar, 2025)
Whenever a person rebels against the religion, the first loss is the loss of peace of mind and happiness. That is why today's modern world is forced to make World Happiness Day and in many countries the Ministry of Happiness has been established regularly. Psychologists are conducting research on these topics and new institutions dedicated to this work courses are also being offered. Despite this, the hearts are unhappy. Islam is a complete code of life and gives full guidance to its followers. The universal teachings of Islam are very clear on these topics such as happiness and peace of mind. But it is important to make these teachings the subject of research and present them to today's world. In this regard, the concept of happiness has been made the subject of research in this article and this concept will be explained in the light of Islamic teachings.
Keywords: Happiness; Concept; Islam; believers